Penggunaan Bakteriofag untuk Kit Detektor Patogen Hawar Bakteri Kedelai - Nurul Rama Dhany; Hardian Susilo Addy; Wiwiek Sri Wahyuni (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2013)
Bacterial blight disease on soybean caused by Pseudomonas syringae pv. glycinea is an important factor causing yield loss in Indonesia. Bacteriophage isolated from irrigation water around the soybean field can be used as indicator for the presence of phytopathogenic bacteria. The objectives of this research was to obtain suitable composition of detector materials to detect P. syringae pv. glycinea using bacteriophage. Composition of detector kit contains of nutrient broth medium with 0.1% of bromothymol blue, 10 g talk and 1 g CMC which will be rubbed on to the detector paper and caused green colour development (pH ± 7) when the paper was dipped on to bacteria suspension, added by a drop of bacteriophage suspension and incubated for 24 hour, the colour will be changed. Yellow color indicated growth activity of P. syringae pv. glycinea where as blue colour indicated suppression of P. syringae pv. glycinea.